Keratinocyte growth factor enhances DNA plasmid tumor vaccine responses after murine allogeneic bone marrow transplantation - Jenq, Robert R. (American Society of Hematology, 2009)
Keratinocyte growth factor (KGF), which is given exogenously to allogeneic bone marrow transplantation (allo-BMT) recipients, supports thymic epithelial cells and increases thymic output of naive T cells. Here, we demonstrate that this improved T-cell reconstitution leads to enhanced responses to DNA plasmid tumor vaccination. Tumor-bearing mice treated with KGF and DNA vaccination have improved long-term survival and decreased tumor burden after allo-BMT. When assayed before vaccination, KGF-treated allo-BMT recipients have increased numbers of peripheral T cells, including CD8(+) T cells with vaccine-recognition potential. In response to vaccination, KGF-treated allo-BMT recipients, compared with control subjects, generate increased numbers of tumor-specific CD8(+) cells, as well as increased numbers of CD8(+) cells producing interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α). We also found unanticipated benefits to antitumor immunity with the administration of KGF. KGF-treated allo-BMT recipients have an improved ratio of T effector cells to regulatory T cells, a larger fraction of effector cells that display a central memory phenotype, and effector cells that are derived from a broader T-cell–receptor repertoire. In conclusion, our data suggest that KGF can function as a potent vaccine adjuvant after allo-BMT through its effects on posttransplantation T-cell reconstitution.